A Community-Based Ecotourism Development Model In Aceh: A Socio-Ecological Perspective - Saprijal Saprijal; Muhammad Junaidi; Lasri Lasri; Fitri Zulfidar; Heri Akmal (Prodi Sosiologi FISIP Universitas Teuku Umar, 2026)
Nature tourism models are one type of local ecotourism-based tourism for communities living in the surrounding area. Nature tourism has amazing prospects due to its beauty, so it needs to be developed in accordance with the potential of the surrounding environment. The purpose of this study is to determine the model for developing Socio-Ecological nature tourism and the sustainable use of nature tourism. The research method used qualitative research, data collection techniques of observation, interviews and documentation. Data analysis techniques included data reduction, data presentation and conclusion drawing. The results of the study show that the development model has attractions, amenities, accessibility and availability of information services, security, and tour guides, opening opportunities for private investment in businesses such as homestays, lodgings/hotels, children's playgrounds and ensuring security. Its utilisation is through face-to-face communication between the Aceh Besar Disparpora government and the management, trust building to achieve commitment, commitment to process, building mutual understanding, preserving nature and the environment, creating job opportunities for the local community such as traders, accommodation providers and photographers, and maintaining the cleanliness and upkeep of the tourist environment.